High temperature spin crossover behaviour of mononuclear bis-(thiocyanato)iron(ii) complexes with judiciously designed bidentate N-donor Schiff bases with varying substituents. Issue 24 (7th June 2022) - Bhar, Kishalay; Guo, Wenbin; Gonidec, Mathieu; Nikhil Raj M, Venkata; Bhatt, Surabhi; Perdih, Franc; Guionneau, Philippe; Chastanet, Guillaume; Sharma, Anuj K.
Abstract : We present herein the solvent and substituent dependent diverse spin crossover behaviours of molecular bis-(thiocyanato)iron(ii ) complexes with smartly designed bidentate Schiff bases above room temperature. Abstract : We present herein a family of molecular cis -[Fe II (X-PPMA)2 (NCS)2 ]·H2 O [4-X- N -(phenyl(pyridin-2-yl)methylene)aniline; X-PPMA; X = –Cl (1 ), –Br (2 ), and –CH3 (3 )] complexes that exhibit spin crossover behaviour above room temperature. Judiciously designed bidentate N-donor Schiff bases of 2-benzoylpyridine and para -substituted anilines in combination with Fe(NCS)2 were used for the synthesis of complexes 1–3 . The relatively strong ligand field of the Schiff bases stabilises the low spin state of iron(II) up to 300 K which is evident from magnetic measurements, room temperature Mössbauer spectra and crystallographic bond/angle distortion parameters. Interestingly, complexes 1–3 crystallize in a tetragonal system with either a P 43 21 2 or P 41 21 2 chiral space group from achiral building units due to the supramolecular helical arrangements of molecules through intermolecular (pyridine)C–H⋯C(NCS) interactions in the crystalline state. Complexes 1 and 2 exhibit complete, gradual and slightly irreversible spin crossover behaviour in the temperature range of 300–500 K with equilibrium temperatures ( T 1/2 ) 375 K (1 ) and 380 K (2 ). The spin state evolution of iron(ii ) in complexes 1 and 2 is monitored between 150 K and 450 K through variable temperature crystallographic studies in the warming mode. The structural data are in good agreement with the 94% (1 ) and 87% (2 ) high spin conversion of iron(ii ) at 450 K. At a high temperature (450 K), some minor irreversible ligand motion is noticed in complexes 1 and 2, in addition to a complete solvent loss that may induce the slight irreversibility of the spin crossover. On the other hand, complex 3 shows a complete and gradual spin crossover in the temperature range of 10–475 K with strong irreversible features. The equilibrium temperatures obtained upon first warming ( T 1/2 ↑) and second cooling ( T 1/2 ↓) are 375 K and 200 K, respectively. In complex 3, the loss of a water molecule triggers strong deviations in the spin crossover behaviour. Moreover, dehydrated complex 3 exhibits photoswitching LIESST effect with a relaxation temperature T(LIESST) = 60 K.